New olenelline trilobites from the Northwest Territories, Canada, and the phylogenetic placement of Judomia absita Fritz, 1973 - Gapp, I. Wesley; Lieberman, Bruce S.; Pope, Michael C.; Dilliard, Kelly A. (Zootaxa, 2011)
The Early Cambrian olenelline trilobites are a diverse clade and have been the subject of several phylogenetic analyses. Here, three new species of Bradyfallotaspis Fritz, 1972 (B. coriae, B. nicolascagei, and B. sekwiensis) and one new species of Nevadia Walcott, 1910 (N. saupeae) are described from the Sekwi Formation of the Mackenzie Mountains, Northwest Territories, Canada. In addition, new specimens potentially referable to Nevadia ovalis McMenamin, 1987 were recovered that may expand that species’ geographic range, which was thought to be restricted to Sonora, Mexico. The results of a phylogenetic analysis incorporating several olenelline taxa, including Judomia absita Fritz, 1973 from the Sekwi Formation, are also presented herein. This species has been assigned to various olenelline genera, including Judomia Lermontova, 1951 and Paranevadella Palmer & Repina, 1993. Phylogenetic analysis suggests this species is closely related to Judomia tera Lazarenko, 1960 from Siberia. This phylogenetic relationship provides further support for the hypothesis that a close biogeographic relationship existed between Laurentia and Siberia during the Cambrian.